1994
DOI: 10.1038/bjc.1994.322
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor expression by human squamous cell carcinomas of the head and neck, cell lines and xenografts

Abstract: S_mmary Epidermal growth factor receptor (EGFR) overexpression has been associated frequently with squamous cell carcinomas (SCC) and SCC cell lines. In most cases the level of EGFR on the tumours from which the cell lines were derived has not been determined, nor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 35 publications
2
53
1
2
Order By: Relevance
“…As a human model epidermoid carcinoma cell line, A431 has been widely used in studies on the cell cycle and tumor related cell signaling pathways because epidermal growth factor receptor (EGFR) is known to be strikingly upregulated in these cells (65)(66)(67)(68). In this study, we found that in the A431 cell, overexpression of PDCD5 inhibits cell proliferation, induces cell cycle arrest at G2/M phase and apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…As a human model epidermoid carcinoma cell line, A431 has been widely used in studies on the cell cycle and tumor related cell signaling pathways because epidermal growth factor receptor (EGFR) is known to be strikingly upregulated in these cells (65)(66)(67)(68). In this study, we found that in the A431 cell, overexpression of PDCD5 inhibits cell proliferation, induces cell cycle arrest at G2/M phase and apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…To address this question, we introduced a single normal copy of human chromosome 4 into two SCC-HN lines that possessed LOH on 4q, BICR6 and BICR31, and two cell lines that did not, BICR3 and BICR19. These cell lines are otherwise matched for p53 (Loughran et al, 1997), p16 INK4A (Loughran et al, 1997), Ras (Clark et al, 1993), epidermal growth factor receptor (Stanton et al, 1994) and chromosome 3 (Loughran et al, 1997) status (Table 1). All the lines are telomerase positive (Loughran et al, 1997).…”
Section: Human Chromosome 4 Specifically Restores Mortality To Scc-hnmentioning
confidence: 99%
“…Although TGF-a expression has also been detected in normal colon (Malden et al, 1989), co-expression of TGF-a and EGFR and growth stimulation by TGF-a has been demonstrated in multiple colon cancer cell lines (Mulder and Brattain, 1989). Overexpression of EGFR has been reported in squamous cell carcinoma of the skin, oesophagus (Itakura et al, 1994;Stanton et al, 1994), non-small-cell lung carcinoma (Rusch et al, 1993), breast adenocarcinoma and endometrial adenocarcinoma (Khalifa et al, 1994;Miller et al, 1994). In colon cancer it has been well documented that overexpression of EGFR may indicate an advanced stage of the disease (Gross et al, 1991) and may predict the metastatic potential (Radinsky et al, 1995).…”
mentioning
confidence: 99%